Exogenous estradiol does not regulate daily metabolic rhythms underlying diet-induced obesity in male mice - W. Brad Osborne; Oliver Vöcking; Victoria M. Alvord; Oluwabukola B. Omotola; Yuriko Katsumata; Julie S. Pendergast (PLoS ONE, 2026)
Male mice fed high-fat diet become obese, but female mice are resistant to diet-induced weight gain. We previously found that circulating estradiol in females protects their daily rhythms from disruption by high-fat feeding to prevent diet-induced obesity. The goal of this study was to determine the effects of estradiol on daily metabolic rhythms in male mice. Male C57BL/6J mice were treated with estradiol and fed high-fat diet for 2 weeks. We measured the effects of high-fat diet feeding on daily rhythms of eating behavior and locomotor activity, and on the phases, or timing, of circadian rhythms in central and peripheral tissues. We found that males treated with estradiol had lower blood glucose when fed high-fat diet than males treated with vehicle even though there were no effects of estradiol treatment on body weight and adiposity. There was no effect of estradiol on the daily rhythm of eating behavior as it was low-amplitude or arrhythmic during high-fat diet feeding in both vehicle- and estradiol-treated males. Locomotor activity rhythms were also unaffected by estradiol treatment. Likewise, the phases of circadian rhythms in the suprachiasmatic nucleus (SCN), liver, muscle, and other peripheral tissues were not altered by estradiol treatment. Thus, treatment of male mice with estradiol did not protect daily rhythms from disruption by high-fat diet, as it does in females. Together these data suggest that the mechanisms underlying sex differences in daily metabolic rhythms are complex and may require both developmental and adult exposure to hormones.